A science mapping analysis of ‘marginality, stigmatization and social cohesion’ in WoS (1963–2019) - Mac Fadden, Isotta; Santana, Monica; Vázquez-Cano, Esteban; López-Meneses, Eloy (Quality & quantity, 2021)
The current socio-economic and politico-humanitarian crisis is reflected in the progressive entanglement of social cohesion. The increase of social, political, and economic vulnerabilities, consequently with the perspective of local human development, make one realize the importance of dimensions such as social capital—and in the networks of relationships according to a perspective of the subject—that occur in a specific urban context where territory is understood as a resource and networks, building new environments of citizen empowerment, avoiding to increase marginal structural contexts. With these premises, this research aims to analyze the scientific production with the greatest impact on the social cohesion crisis, interpreted as a consequence of advanced marginality, a complex set of economic, political, and socio-structural vulnerabilities in relation to stigmatization, a key element in the vulnerability of subjects. SciMAT, a bibliometric science mapping software tool based on co-word analysis and h-index, is applied using a sample of 4297 articles from 1963 to 2018 published in 1119 journals main communication in the database Web of Science. The results show how social exclusion and stigma are strongly related to the understanding of the constant increase in social vulnerabilities.